O‘zbekistonda kichik biznes subyektlarini samarali moliyalashtirish: muammolar va yechimlar (Biznesni rivojlantirish banki ATB misolida) - Usanov Ilhom Bahodirovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article examines the issues of effective financing of small business entities by banks in Uzbekistan, the existing challenges, and ways to overcome them. The study analyzes the experience of small business lending through the example of the Business Development Bank ATB and compares it with international practices. The article provides recommendations for enhancing the efficiency of the banking system in supporting small enterprises.